2019
DOI: 10.33635/sitefa.v2i1.90
|View full text |Cite
|
Sign up to set email alerts
|

Benefícios Da Implantação Do Programa De Compliance Em Uma Organização Do Setor De Energia

Abstract: Uma pesquisa pautada em um termo amplamente difundido nos dias de hoje em todo o mundo e em diversas esferas da sociedade. No Brasil o compliance ainda é recente, mas aos poucos está ganhando espaço, principalmente em alguns segmentos do setor privado. A pesquisa foi idealizada com o intuito de compreender a necessidade das empresas em promover a inclusão do programa e o ganho obtido. Neste trabalho, foi considerada uma empresa do setor de energia, por ser este setor o que desempenha maior aderência na implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These results are corroborated by authors such as França and Leismann [80] (p. 132) who, in relation to harmful acts, say that 'knowing and accepting the risks of each area it is possible to plan preventive acts". Other studies [11,20,21,24) identified positive relationships between the audit committee, information symmetry and decision optimization. In agreement, the study by Azevedo [9], Valência, Queiruga, and González-Benito [15], Hasnan et al [16], Charles and Kim [17], Yeo, Chong, and Carter [18], Hommerová and Severová [19] and Lacruz et al [22] found that the increase in donation levels resulted from corporate governance, internal controls and compliance practices.…”
Section: Adequacy Of Management Practices Regarding the Organizationa...mentioning
confidence: 99%
See 2 more Smart Citations
“…These results are corroborated by authors such as França and Leismann [80] (p. 132) who, in relation to harmful acts, say that 'knowing and accepting the risks of each area it is possible to plan preventive acts". Other studies [11,20,21,24) identified positive relationships between the audit committee, information symmetry and decision optimization. In agreement, the study by Azevedo [9], Valência, Queiruga, and González-Benito [15], Hasnan et al [16], Charles and Kim [17], Yeo, Chong, and Carter [18], Hommerová and Severová [19] and Lacruz et al [22] found that the increase in donation levels resulted from corporate governance, internal controls and compliance practices.…”
Section: Adequacy Of Management Practices Regarding the Organizationa...mentioning
confidence: 99%
“…Non-profit organizational behavior has been the subject of recent national and foreign research [9,15,16,17,18,19,20,21,22,23,24], institutional theory and resource dependence have been used as theoretical structures to explain several aspects of organizational structure and performance. Lacruz [23] (p. 2) investigated the adoption and formalization of management practices based on corporate governance and concludes that the adoption of compliance practices makes these organizations "to be considered more attractive to donors and, consequently, receive more resources in donation".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-profit organizational behavior has been the subject of recent national and foreign research [9,48,49,[63][64][65][66][67][68][69][70] that highlight integrity as a compliance principle of business ethics and corporate governance. Such investigations are based on institutional theory and resource dependence and have been used as theoretical structures to explain several aspects of organizational structure and performance.…”
Section: Studies On Compliance In the Third Sectormentioning
confidence: 99%
“…Lacruz [70] (p. 2) investigated the adoption and formalization of management practices based on corporate governance and concludes that the adoption of compliance practices makes these organizations "to be considered more attractive to donors and, consequently, receive more resources in donation". For Senno et al [68] (p. 225), compliance "is the principle of corporate governance that gives sustainability to relations, enabling and favoring that all stakeholders are respected". In agreement, Candeloro, Rizzo and Pinho [58] (p. 454) define compliance as "a set of rules, standards, ethical and legal procedures, which, once defined and implemented, will be the main line that will guide the institution's behavior in the market in which it operates, as well as the attitude of their employees".…”
Section: Studies On Compliance In the Third Sectormentioning
confidence: 99%